Dampak Klorofluorokarbon Terhadap Lingkungan Hidup - Sumingkrat Sumingkrat (Balai Besar Kimia dan Kemasan, 1998)
As the first step in tackling environmental issues related to the protection of the ozone layer have been reviewed internationally. In Indonesia under the